Efficacy of botulinum toxin in treatment of bruxism and temporomandibular disorders. Systematic review - Swacha, Weronika; Pikulicka, Agata; Szulc, Izabela; Pacek, Katarzyna; Piekarska, Małgorzata; Kasperski, Radosław; Jedlina, Klaudia; Rusin, Klaudia; Budziłło, Julia; Dobrzańska, Justyna (Journal of Education, Health and Sport, 2023)
The medical use of botulinum toxin nowadays is widespread. Recent years show that use of botulinum toxin is not only used to control the muscular overactivity in bruxism, tension in temporomandibular disorders but also it can be applied for cosmetic reasons. The objective of this study was to view recent discoveries in this subject by conducting a systemic review of clinical trials published in the research works. Recent studies present efficacy in releasing pain in both: bruxism and temporomandibular disorders by minimizing symptoms and reducing the intensity of muscle contractions. The scientific works cited confirm a noticeable improvement in most symptoms occurring in the states mentioned above.